2020
DOI: 10.4049/jimmunol.1900575
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab Interferes with the Differentiation of Human FOXP3+–Induced T Regulatory Cells, but Not with FOXP3 Stability, through Activation of mTOR

Abstract: Programmed cell death 1 (PD-1) is critical for T regulatory cells (Tregs) to maintain peripheral tolerance to self-antigens. In the tumor microenvironment, interaction between PD-1 and its ligands supports tumor immune evasion. Pembrolizumab blocks interactions of PD-1 with its ligands, enhancing antitumor and clinical responses. We and others have reported that pembrolizumab does not affect function or phenotype of thymic-derived Tregs; however, little is known about its effect on extrathymic differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…Therefore, we investigated the effects of different ICIs on tumor-infiltrating FoxP3 + Tregs in breast cancer patients. We have previously reported that anti-PD-1 (pembrolizumab) does not affect the phenotype or function of Tregs, as it instead affects the differentiation of FoxP3 + -induced Tregs [17,18]. In the present study, we found that the levels of FoxP3 + Helios + Treg remained unaffected upon the treatment with anti-PD-1.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Therefore, we investigated the effects of different ICIs on tumor-infiltrating FoxP3 + Tregs in breast cancer patients. We have previously reported that anti-PD-1 (pembrolizumab) does not affect the phenotype or function of Tregs, as it instead affects the differentiation of FoxP3 + -induced Tregs [17,18]. In the present study, we found that the levels of FoxP3 + Helios + Treg remained unaffected upon the treatment with anti-PD-1.…”
Section: Discussionsupporting
confidence: 54%
“…Unlike anti-TIM-3 mAb, pembrolizumab treatment resulted in a complete blockade of the PD-1 surface expression on T cell subsets; this complete blockade was most likely due to a "masking effect" blocking the epitope of PD-1 by pembrolizumab, so the fluorescence-activated cell sorting (FACS) detection antibody would not be able to bind the same epitope of PD-1 showing no expression. This justification was supported and confirmed by qPCR and Western plot data indicating that pembrolizumab does not alter the expression of PD-1 at the mRNA and protein levels, as it only blocks its epitope [17].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The results were analogous when PD-1 was blocked with a mAb. On the other hand, Nair et al described inhibition of peripheral FoxP3 T-reg cells differentiation and a FoxP3 down-regulation through mTOR pathway under pembrolizumab-mediated PD-1 blockade [52]. The treated T-cells were less suppressive, but the study has not been validated in vivo.…”
Section: Pd-1+ T-reg Expansion -Immunosuppresionmentioning
confidence: 99%